Addressing the Gap: Occupational Therapy in Hospice Care. Issue 2 (1st April 2021) - Mueller, Emily; Arthur, Paul; Ivy, Mack; Pryor, Loree; Armstead, Amber; Li, Chih-Ying
Abstract: Patients receiving hospice care have a host of occupational challenges, though few are being seen in occupational therapy for treatment. Occupational therapy can help those receiving hospice care live with dignity before death. Data retrieved from the National Home and Hospice Care Survey were analyzed using independent t-tests, Wilcoxon rank-sum tests, Chi-square tests and logistic regressions. Only 10.6% of the participants received occupational therapy. Patients who received occupational therapy were significantly older and had shorter lengths of hospice care service compared to their counterparts. Over 85% of the patients needed assistance with at least one task of activity of daily living (ADL). Findings suggested a need to increase occupational therapy workforce in hospice care and advocate the value of occupational therapy services in hospice settings.